2018
DOI: 10.1038/s41598-018-30943-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of probiotic Bifidobacterium bifidum G9-1 on the relationship between gut microbiota profile and stress sensitivity in maternally separated rats

Abstract: Although gut microbiota and early life events are likely involved in the development of irritable bowel syndrome (IBS), it remains unclear how these factors interact in the pathophysiology of IBS. In the present study, using rats subjected to maternal separation (MS) as a model of IBS, we investigated interrelationships among gut microbiota, stress susceptibility and intestinal permeability, and examined the effect of the probiotic Bifidobacterium bifidum G9-1 (BBG9-1) on those interrelationships. When compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 41 publications
2
64
0
Order By: Relevance
“…Accumulating evidence has suggested that alteration in the gut microbiota is associated with the development of metabolic, psychological, and gastrointestinal functional disorders [ 11 , 12 , 13 , 14 ]. However, it has remained largely unknown how gut dysbiosis is involved in the pathophysiology in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that alteration in the gut microbiota is associated with the development of metabolic, psychological, and gastrointestinal functional disorders [ 11 , 12 , 13 , 14 ]. However, it has remained largely unknown how gut dysbiosis is involved in the pathophysiology in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we note a greater impact of all dietary interventions on the gut microbiota than early‐life stress. Others have shown differences in the composition of the microbiota on postnatal day 20 that were amenable to microbial manipulation, but these were no longer evident in adulthood (Fukui et al., ). Similar to our study, differences in behaviour between MS and NS rats were noted in adulthood without linking to large differences in the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 500 ÎŒL of whole blood was collected in 1.5-mL microcentrifuge tubes containing 10 ÎŒL of EDTA (ethylenediaminetetraacetic acid). The serum was obtained by centrifugation for 10 min in a refrigerated centrifuge at 4 °C and stored at −80 °C for further analysis [ 32 , 33 ]. The serum corticosterone level was quantified using a commercially available corticosterone ELISA kit (Arigo, ARG80652, Hsinchu, Taiwan, China), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%